Synergistic modification of hot-melt extrusion and nobiletin on the multi-scale structures, interactions, thermal properties, and in vitro digestibility of rice starch - Zhang, Zhihong; Feng, Ying; Wang, Honglan; He, Hai (Frontiers in Nutrition, 2024)
This work examines the effects of hot-melt extrusion (HME) and nobiletin (NOB) on the multi-scale structure, interaction, thermal, and digestibility characteristics of rice starch. HME disrupted the crystalline structure, helix structure, short-ordered structure, and thermal characteristics of starch.However, the incorporation of NOB leads to a highly single-helical and V-shaped crystal structure with the formation of ordered structural domains. Based on density functional theory calculations and the infrared second derivative of a Fourier-transform infrared spectrometer, it was determined that NOB binds to starch through hydrophobic interactions and hydrogen bonds, thereby preventing starch molecular chains from interacting with each other and destroying their double helix structure. The combination of synergistic treatment resulted in an enhancement of ordered structure and thermal stability. As a result, this led to an increase in resistant starch and slowly digested starch. Therefore, this work provides the theoretical and experimental basis for creating superior rice starch products.